Unveiling the complexities: A case report on complications arising from propionic acidemia - Imran Uddin; Rafat Jan (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Propionic acidemia is a rare inherited metabolic disorder caused by a defect in propionyl-coenzyme A (CoA) carboxylase, resulting in the accumulation of propionic acid. We present a case involving a 5-year-old male with a known history of propionic acidemia who presented to the emergency department with decreased oral intake, vomiting, and diarrhea. Despite initial interventions, the patient developed severe metabolic acidosis, respiratory distress, and gastrointestinal symptoms. The case highlights the varied complications of propionic acidemia, including cardiac complications, intellectual difficulties, and recurrent respiratory distress. The patient's course involved intensive care management, including mechanical ventilation and cardiac support. This report contributes to the understanding of the multifaceted challenges posed by propionic acidemia and emphasizes the importance of a multidisciplinary approach in the management of this rare metabolic disorder.